Każde dziecko i każda jego cecha ma swoiste tempo rozwoju, modyfikowane przez warunki życia w danym okresie. (Raport 2 z dwuletnich comiesięcznych badań na Jukatanie w Meksyku) - Napoleon Wolański; Armando Rojas; Graciela Valentin; Anna Siniarska (Studia Ecologiae et Bioethicae)
In the first report, the specific monthly rate of changes of body build measures, typical for a studied group of youths and /or seasonal changes according to climatic conditions were not observed (Siniarska et al., 2005). The preliminary results suggested that observed changes rather depend on an adjustment to conditions and mode of life than to changes in nature. In the present report changes in particularly studied individuals were analyzed to verify the previous hypothesis suggesting that the rate of development has an immediate (causal) sense. The problem of whether the pubertal spurt is a single developmental effort or series of changes with dominance of intensified increments was considered. To explain the phenomenon of difference in onset of the pubertal spurt and its intensity in various populations, monthly measurements were conducted in individuals being at the age of puberty. The results show that each individual and its variable show a different rate of changes. It suggests that the rate of development and changes in body mass and fat mass are occasional. It rather depends on living conditions, mostly on nutrition and mode of life (physical activity and leisure). The only regularity shows that rather short (1-3 months) periods of rapid growth (saltations) are divided by slower growth periods (stasis), but their duration and time of occurrence have a very individual character. The rate and rhythm of each body build variables are also different. These phenomena depend rather on condition s in which the development of each individual occurs, as well as on its genetic predispositions and eco-sensitivity. It is probable, that differences in onset and intensity of pubertal spurt depend on alternations between periods of saltations and stasis of growth processes and on changes in body mass. These studies need to be repeated during a longer period of time (at least within a 5-year period ), in different climatic conditions and social groups.